Properties of stainless-steel surface after hollow cathode assisted plasma nitriding - Zhehao Zhang; Yongjie Bi; Minyi Zhang; Yang Li; Fushuai Zhao; Shangzhou Zhang; Yongyong He (Materials Research Express, 2020)
AISI 304 stainless steel was nitrided at different temperature in the plasma equipment using a new auxiliary device. The proposed hollow cathode auxiliary device improves the plasma density, thereby accelerating the nitriding process. The modified surface was characterized by x-ray diffraction, scanning and transmission electron microscopies, atomic force microscopy, surface microhardness testing. Electrochemical corrosion test was used to measure the localized corrosion resistance of the samples. Single S-phase layer without the CrN precipitation was obtained by hollow cathode plasma nitriding at 450 °C, which improved the microhardness, wear and corrosion resistance of the steel surface. Nitriding at higher temperature of 550 °C resulted in substitution of the S-phase towards layer composed from CrN and α -Fe phases, improving the microhardness but decreasing the corrosion resistance.